Strain-dependent vibrational spectra and elastic modulus of poly(p-phenylene terephtalamide) from first-principles calculations. (5th May 2017) - Avanzini, Lorenzo; Brambilla, Luigi; Marano, Claudia; Milani, Alberto
Abstract: A periodic Density Functional Theory investigation of the structural and spectroscopic properties of poly(p-phenylene terephthalamide) (PPTA), carried out by means of CRYSTAL14, is here reported, for both the three-dimensional crystal and the isolated polymer chain treated as a infinite one-dimensional crystal focusing in particular on strain-dependent Raman spectra. Parallel to the theoretical investigation, spectroscopic measurements have been carried out on undeformed samples and during mechanical testing. In addition to the detailed assignment of the vibrational spectra, polarized IR spectra are also computed and compared to the experimental ones, giving information for the characterization of the orientation properties of PPTA. Finally, the elastic modulus of PPTA is computed for the ideal crystal and the infinite chain and compared to the experimental values reported in the literature. This work shows how a combined experimental/computational approach can give an accurate interpretion of the structural evolution and vibrational spectra of PPTA under strain, providing an effective method to rationalize structure/properties correlations on the basis of the peculiar intra and intermolecular interactions taking place in the fiber. Graphical abstract: Highlights: The crystal structure, spectroscopic and mechanical propertied of PPTA have been investigated. State-of-the-art periodic DFT calculations are applied to polymers' crystals. Strain-dependent Raman spectra of PPTA have been predicted by quantum chemical calculations. The ultimate elastic moduls of PPTA have been predicted.